Optimisation of the bioreduction process of carbonyl compounds promoted by seeds of glossy privet (Ligustrum lucidum - Oleaceae) and its application to the synthesis of key intermediates. Issue 1 (2nd January 2021) - Bordón, Daniela L.; Vázquez, Ana M.; Decarlini, María F.; Demmel, Gabriela I.; Rossi, Laura I.; Aimar, Mario L.
Abstract: The fruits of Ligustrum lucidum were used as an efficient biological reducer of carbonyl compounds, and trials were carried out to optimise the reductive process using acetophenone as the model substrate. In order to try to eliminate the dependence on the seasonal production of the fruits, a study was carried out to find ways to conserve them. The results reported here show that it is possible to store the dehydrated fruits of glossy privet at room temperature over a prolonged period of time, during which time they can be used as a common chemical reagent. On the other hand, studies performed on different parts of the fruits established that the seeds are responsible for the bioreduction process, with the best reduction conditions found being isolated seeds from the fruits of glossy privet at 25 °C, in a 100 mM phosphate buffer pH 6.0, using 0.67% w/v of DMSO as co-solvent with an acetophenone charge of 2.67 g/L (22 mM). Moreover, seed reuse studies showed that it is possible to recycle them, providing almost the same activity and enantioselectivity from the first to the fifth cycle, without any loss of biocatalytic properties. Finally, using whole seeds of glossy privet in optimal reaction conditions, important alcohols useful as key intermediates in the synthesis of industrial products were obtained on a laboratory scale through the reduction of specially selected ketones and aldehydes.